Analysis of Water Quality Around the Fishpond Area, Citarum Watersheds, Karawang Regency: english - Komarudin, Nurul Amri; Rakhman, Selly Arvinda; Tubal, Jairus Jesse M. (Teknik Lingkungan Universitas Islam Indonesia, 2026)
This research was conducted to provide data on water quality based on physical and chemical parameters around the fishpond area, Citarum Watersheds, in Karawang Regency. Water quality is a primary requirement for the sustainability of local economic activities. However, with the increasing pollution load, there is concern that water quality around the fishpond area will decline, impacting fishpond productivity, public health, and the environment. Water samples were collected at 10 points along the Citarum Watersheds using a water quality test pen. The measured physico-chemical parameters included temperature, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), pH, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). The results indicate that several physico-chemical parameters still do not meet the quality standards established by Government Regulation (PP) Number 22 of 2021. These include BOD and DO, where concentrations at all observation points exceeded the quality standards, while the COD values exceeded the standard at most points, except at stations 1-5. This exception is due to their considerable distance from agricultural activities or other community practices. The high COD concentration indicates a significant load of organic pollutants, which are suspected to originate from agricultural runoff and domestic waste. Conversely, the low DO concentration is caused by microorganisms in the water body utilizing the oxygen. These microorganisms require DO as an electron acceptor in their metabolic processes, leading to a decrease in DO levels in the water and a corresponding increase in BOD. The BOD/COD ratio at the study site ranged from 0.46 to 0.5, meaning the pollutants are categorized as biodegradable. Therefore, it can be concluded that the waters in the downstream region of the Citarum River are still suitable for use in freshwater aquaculture activities.